ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBATALAN PEMBIAYAAN MURABAHAH PADA BANK 9 JAMBI SYARIAH - Nur Alifah (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2023)
This study aims to analyze the factors that influence the cancellation of murabahah financing at Bank 9 Jambi Syariah. Bank 9 Jambi Syariah or known to the public as Bank Jambi Syariah is a sharia branch office located on Jl. Captain Pattimura, Simpang IV Sipin, Telanaipura, Jambi. One of the financing products offered and distributed by Bank 9 Jambi Syariah is the murabahah financing product. Murabahah financing is a financing or sale and purchase agreement of goods by stating the acquisition price and profit (margin) agreed upon by the seller and the buyer. The formulation of the problem in this research is: what are the stages of the murabahah financing process? What are the factors that affect the cancellation of murabaha financing?This research is a field research using qualitative methods which was carried out at Bank 9 Jambi Syariah. This research also uses library research such as books, journals, and so on. In this research the author uses the method of observation, interviews, and documentation. Where interviews were conducted by employees and customers of Bank9 Jambi Syariah. From the results of research conducted by the author, it is known that in the 2017-2021 period the number of murabahah financing reached 782 customers and the percentage of financing cancellations was 1.6%. Factors causing the cancellation of murabahah financing were due to problematic SLIK, business feasibility, and non-compliance with requirements.